A Comparative Analysis of Gene and Protein Expression Throughout a Full 28-Day Retinal Regeneration Time-Course in Adult Zebrafish - Kramer, Ashley C.; Gurdziel, Katherine; Thummel, Ryan (Frontiers in Cell and Developmental Biology, 2021)
Following photoreceptors ablation by intense light exposure, adult zebrafish are capable of complete regeneration due to the ability of their Müller glia (MG) to re-enter the cell cycle, creating progenitors that differentiate into new photoreceptors. The majority of previous reports on retinal regeneration focused on the first few days of the regenerative response, which include MG cell-cycle re-entry and progenitor cell proliferation. With this study, we analyzed the full 28-day time-course of regeneration by pairing a detailed morphological/immunological analysis with RNA-seq transcriptional profiling at 8 key time points during retinal regeneration. We observed several novel findings. First, we provide evidence for two separate peaks of MG gliosis, with the secondary gliotic peak occurring after MG cell-cycle re-entry. Second, we highlight a distinct transcriptional shift between 5- and 10-days post lesion that highlights the transition from progenitor proliferation to differentiation into new photoreceptors. Third, we show distinctly different patterns of transcriptional recovery of the photoreceptor opsins at 28 days post lesion. Finally, using differential gene expression analysis, we revealed that the established functional recovery of the retina at 28 days post lesion does not, in fact, return to an undamaged transcriptional state, potentially redefining what the field considers complete regeneration. Together, to our knowledge, this work represents the first histological and transcriptomic map of a 28-day time-course of retinal regeneration in adult zebrafish.